Hepatic abnormalities in youth with Turner syndrome. (16th July 2022) - Singh, Isani; Noel, Gillian; Barker, Jennifer M.; Chatfield, Kathryn C.; Furniss, Anna; Khanna, Amber D.; Nokoff, Natalie J.; Patel, Sonali; Pyle, Laura; Nahata, Leena; Cole, Francis S.; Ikomi, Chijioke; et al.
Abstract: Background & Aims: Liver disease in children with Turner Syndrome (TS) is poorly understood relative to associated growth, cardiac and reproductive complications. This study sought to better characterize hepatic abnormalities in a large national cohort of youth with TS. Methods: Using electronic health record data from PEDSnet institutions, 2145 females with TS were matched to 8580 females without TS on eight demographic variables. Outcomes included liver enzymes (AST and ALT) stratified as normal, 1–2 times above the upper limit of normal (ULN), 2–3 times ULN and >3 times ULN, as well as specific liver disease diagnoses. Results: Fifty‐eight percent of youth with TS had elevated liver enzymes. Patients with TS had higher odds of enzymes 1–2 times ULN (OR: 1.7, 95% CI: 1.4–1.9), 2–3 times ULN (OR: 2.7, 95% CI: 1.7–3.3) and >3 times ULN (OR: 1.7, 95% CI: 1.3–2.2). They also had higher odds of any liver diagnosis (OR: 2.4, 95% CI: 1.7–3.3), fatty liver disease (OR: 1.9, 95% CI: 1.1–3.2), hepatitis (OR: 3.7, 95% CI: 1.9–7.1), cirrhosis/fibrosis (OR: 5.8, 95% CI: 1.3–25.0) and liver tumour/malignancy (OR: 4.8, 95% CI: 1.4–17.0). In a multinomial model, age, BMI and presence of cardiovascular disease or diabetes significantly increased the odds of elevated liver enzymes in girls with TS. Conclusions: Youth with TS have higher odds for elevated liver enzymes and clinically significant liver disease compared with matched controls. These results emphasize the need for clinical screening and additional research into the aetiology and treatment of liver disease in TS. Lay summary: Turner Syndrome, a chromosomal condition in which females are missing the second sex chromosome, is often associated with short stature, infertility and cardiac complications. Liver abnormalities are less well described in the literature. In this study, nearly 60% of youth with TS have elevated liver enzymes. Furthermore, patients with TS had a diagnosis of liver disease more often than patients without TS. Our results support the importance of early and consistent liver function screening and of additional research to define mechanisms that disrupt liver function in paediatric TS females.